The benefits of using a vacuum-assisted socket system to improve balance and gait in elderly transtibial amputees. (February 2016) - Samitier, C Beatriz; Guirao, Lluis; Costea, Maria; Camós, Josep M; Pleguezuelos, Eulogio
Background: Lower limb amputation leads to impaired balance, ambulation, and transfers. Proper fit of the prosthesis is a determining factor for successful ambulation. Vacuum-assisted socket systems extract air from the socket, which decreases pistoning and probability of soft-tissue injuries and increases proprioception and socket comfort. Objectives: To investigate the effect of vacuum-assisted socket system on transtibial amputees' performance-based and perceived balance, transfers, and gait. Study design: Quasi-experimental before-and-after study. Methods: Subjects were initially assessed using their prosthesis with the regular socket and re-evaluated 4 weeks after fitting including the vacuum-assisted socket system. We evaluated the mobility grade using Medicare Functional Classification Level, Berg Balance Scale, Four Square Step Test, Timed Up and Go Test, the 6-Min Walk Test, the Locomotor Capabilities Index, Satisfaction with Prosthesis (SAT-PRO questionnaire), and Houghton Scale. Results: A total of 16 unilateral transtibial dysvascular amputees, mean age 65.12 (standard deviation = 10.15) years. Using the vacuum-assisted socket system, the patients significantly improved in balance, gait, and transfers: scores of the Berg Balance Scale increased from 45.75 (standard deviation = 6.91) to 49.06 (standard deviation = 5.62) ( p  < 0.01), Four Square Step Test decreased from 18.18 (standard deviation = 3.84) s to 14.97 (3.9) s ( p  < 0.01), Timed Up and Go Test decreased from 14.3 (standard deviation = 3.29) s to 11.56 (2.46) s ( p  < 0.01). The distance walked in the 6-Min Walk Test increased from 288.53 (standard deviation = 59.57) m to 321.38 (standard deviation = 72.81) m ( p  < 0.01). Conclusion: Vacuum-assisted socket systems are useful for improving balance, gait, and transfers in over-50-year-old dysvascular transtibial amputees. Clinical relevance: This study gives more insight into the use of vacuum-assisted socket systems to improve elderly transtibial dysvascular amputees' functionality and decrease their risk of falls. The use of an additional distal valve in the socket should be considered in patients with a lower activity level.